Victorian poetry : poetry, poetics, and politics (Routledge, 1993)
In a work that is uniquely comprehensive and theoretically astute, Isobel Armstrong rescues Victorian poetry from its longstanding sepia image as 'a moralised form of romantic verse', and unearths its often subversive critique of nineteenth-century culture and politics.